2020
DOI: 10.2147/ijwh.s242864
|View full text |Cite
|
Sign up to set email alerts
|

<p>Burden of Menstrual Pain Measured by Heatmap Visualization of Daily Patient-Reported Data in Japanese Patients Treated with Ethinylestradiol/Drospirenone: A Randomized Controlled Study</p>

Abstract: Purpose: Dysmenorrhea negatively affects women's quality of life and poses a considerable economic burden. A recent study in Japanese patients with dysmenorrhea (NCT01892904) reported a significant reduction in the number of days with menstrual pain after treatment with a flexible extended regimen of ethinylestradiol (EE)/drospirenone (DRSP) compared with a cyclic regimen. However, individual patients' menstrual pain patterns and intensities were not indicated. Heatmapping was used to visualize menstrual pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Our study showed that the cyclic LEP regimen relieved pelvic pain and burdensome symptoms due to dysmenorrhea. However, cyclic regimens allow hormone withdrawal bleeding to occur at regular intervals, and it is known that pain due to dysmenorrhea generally peaks around the time of menstruation [ 26 ]. An extended LEP regimen available in Japan makes it possible to take EE/DRSP or levonorgestrel/EE for up to 120 and 77 days, respectively, resulting in a reduced menstrual frequency, which may reduce the number of painful episodes for patients with dysmenorrhea and may limit situations in which patients miss work or school.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that the cyclic LEP regimen relieved pelvic pain and burdensome symptoms due to dysmenorrhea. However, cyclic regimens allow hormone withdrawal bleeding to occur at regular intervals, and it is known that pain due to dysmenorrhea generally peaks around the time of menstruation [ 26 ]. An extended LEP regimen available in Japan makes it possible to take EE/DRSP or levonorgestrel/EE for up to 120 and 77 days, respectively, resulting in a reduced menstrual frequency, which may reduce the number of painful episodes for patients with dysmenorrhea and may limit situations in which patients miss work or school.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the estrogen and progestin sequential therapy, drospirenone and ethinylestradiol tablets are lower in ethinylestradiol and have fewer side effects, which ensures patient safety. A recent study [ 18 ] in patients with dysmenorrhoea found a significant reduction in the number and intensity of days of menstrual pain in patients treated with the ethinylestradiol (EE)/drospirenone (DRSP) regimen compared to sequential therapy. In this result, the duration of abdominal pain was shorter in group A patients than in group B after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven studies ( 6 13 , 17 22 ) were included involving 2,251 participants. There were 10 English studies ( 6 10 , 12 , 13 , 17 22 ) and one Chinese study ( 11 ). Six studies ( 6 – 9 , 11 , 12 , 17 – 19 ) were RCTs ( n = 1534), one ( 13 ) was a non-randomized control study ( n = 43), and four studies ( 10 , 20 22 ) were single-arm studies ( n = 674).…”
Section: Resultsmentioning
confidence: 99%
“…Two of the studies ( 11 , 21 ) were single center studies, whereas nine studies ( 6 10 , 12 , 13 , 17 20 , 22 ) were multicenter studies. The study subjects were primary dysmenorrhea patients (three studies) ( 8 , 11 , 13 , 18 , 19 ), endometriosis patients (three studies) ( 12 , 20 , 22 ), and both primary dysmenorrhea and secondary dysmenorrhea patients (four studies) ( 6 10 , 17 ). One study ( 20 ) did not specify the type of dysmenorrhea.…”
Section: Resultsmentioning
confidence: 99%